2002
DOI: 10.1016/s1534-5807(01)00097-1
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Sog Morphogen Gradient in the Drosophila Embryo

Abstract: A variety of genetic evidence suggests that a gradient of Decapentaplegic (Dpp) activity determines distinct cell fates in the dorsal region of the Drosophila embryo, and that this gradient may be generated indirectly by an inverse gradient of the BMP antagonist Short gastrulation (Sog). It has been proposed that Sog diffuses dorsally from the lateral neuroectoderm where it is produced, and is cleaved and degraded dorsally by the metalloprotease Tolloid (Tld). Here we show directly that Sog is distributed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 59 publications
3
89
0
Order By: Relevance
“…Indeed, Sog protein is enriched in the apical side (toward the outside) of the cells that secrete it in the blastoderm embryo (53). In another study, anti-GFP antibodies microinjected into the perivitelline space were shown to be transported together with Dpp-GFP and concentrated on BMP receptors in the dorsal-most cells of the embryo (54).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, Sog protein is enriched in the apical side (toward the outside) of the cells that secrete it in the blastoderm embryo (53). In another study, anti-GFP antibodies microinjected into the perivitelline space were shown to be transported together with Dpp-GFP and concentrated on BMP receptors in the dorsal-most cells of the embryo (54).…”
Section: Discussionmentioning
confidence: 97%
“…Sog is required to shuttle BMPs (called "Dpp" and "Screw") to the dorsal side to achieve maximal signaling (51,52). Endogenous Sog protein has been shown to diffuse at a distance from its source during Drosophila D-V patterning (53). However, Sog protein was only detected in dorsal blastoderm cells after its endocytosis, as the method used did not allow direct staining in the outer ECM itself.…”
Section: Discussionmentioning
confidence: 99%
“…3C; Francois and Bier 1995). The secreted SOG protein forms a long-range inverse gradient to DPP with high levels ventrolaterally and low levels dorsally (Srinivasan et al 2002). Ventrolaterally, high levels of SOG bind and inhibit DPP (Ferguson and Anderson 1992;Biehs et al 1996).…”
Section: Decapentaplegic Gradient Formationmentioning
confidence: 99%
“…Therefore, through antagonism of DPP signaling, the SOG gradient modulates the DPP gradient. Recent evidence has suggested that the gradient of SOG is also regulated by endocytosis (Srinivasan et al 2002). In the wild type, dorsal levels of SOG are generally low, with higher levels near the ventral source.…”
Section: Decapentaplegic Gradient Formationmentioning
confidence: 99%
“…Direct support for the hypothetical Sog gradient in dorsal cells has recently been obtained by histochemical methods (Srinivasan et al, 2002). As predicted, Tolloid proteolysis limits the accumulation of Sog dorsally, which is required to form a stable concentration gradient of Sog.…”
Section: Sog and Chordin Also Act As Long-range Morphogens In The Nonmentioning
confidence: 74%